The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5455/jmood.20120208025502
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between insomnia and major depressive disorder: a chicken and egg situation?

Abstract: ÖZET:Uykusuzluk ve majör depresif bozukluk arasında-ki bağlantı: Bir tavuk ve yumurta durumu mudur?Majör depresif bozukluk (MDB) çok yaygın, şiddetle güç-süz düşürücü ve sıklıkla da yineleyicidir. MDB'li bireylerin önemli bir kısmı uyku düzensizliklerinden yakınırlar. MDB aynı zamanda çeşitli uyku bozukluklu kitleler arasında fazla miktarda temsil edilmektedir. Uyku düzensizlikleri MDB'nin tipik özelliklerinden olsa da, böyle belirtiler bazen bir MDB döneminden önce ortaya çıkarlar. Uyku düzensizliği, özellikl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Due to the bidirectional relationship between depressive symptoms and sleep disturbances, it is difficult to identify the cause and effect. However, it has been suggested that the combination of insomnia and depression influences the severity and duration of MDD as well as relapse rates, whereas pharmacological and nonpharmacological interventions for insomnia may favorably reduce and possibly prevent MDD (8). Therefore, early identification of adolescents with sleeping problems may prevent a depression in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the bidirectional relationship between depressive symptoms and sleep disturbances, it is difficult to identify the cause and effect. However, it has been suggested that the combination of insomnia and depression influences the severity and duration of MDD as well as relapse rates, whereas pharmacological and nonpharmacological interventions for insomnia may favorably reduce and possibly prevent MDD (8). Therefore, early identification of adolescents with sleeping problems may prevent a depression in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This two-way relationship between sleep disturbances and MDD makes it difficult to establish a cause-and-effect connection between them. Longitudinal studies have defined sleep disorders as a risk factor for new onset or recurrent MDD development, and this relationship has been shown in young adult, middle-aged, and elderly populations (8).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal sleep, in both chronic and acute situations, has been linked to such adverse physical conditions as coronary heart disease, hypertension, obesity, and all-cause mortality (Ayas et al, 2003; Gottlieb et al, 2006; Patel et al, 2004; Taheri et al, 2004). Poor sleep has also been associated with negative psychological aspects such as pain perception, posttraumatic stress disorder (PTSD), and major depressive disorder (Gulec et al, 2012; Pieh et al, 2011; Van Liempt, 2012).…”
mentioning
confidence: 99%
“…Moreover, drugs and behavioral treatments for comorbid MDD and insomnia symptoms can improve both outcomes [8,9]. Therefore, the relationship between MDD and insomnia may be bi-directional [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the underlying mechanism of MDD remains elusive, MDD is recognized as a complex disorder contributed by both genetic and environmental factors. The heritability of MDD is 40% to 50% suggested by twin studies [11]. However, the genetic component of insomnia is hard to estimate because it can coexist with other medical and psychiatric conditions.…”
Section: Introductionmentioning
confidence: 99%